A Secured and Controlled Billing System by Agent for Cloud Computing Environment (International Journal of Engineering and Computer Science, 2014)
Day by day the use of cloud computing is increasing, so it is challenging task for cloud service provider to provide services and maintain data of provided service of cloud storage in very secure way for generation of bill .the transaction should be reliable effective trustworthy. There should be no interrupt in transaction. In previous system cloud faces many security issues and is considered unreliable by the client because of inflexible communication between CSP and client. In this paper, we propose billing system which provide effective and trust worthy solution for such problems .The system uses concept of CTA for confirmation of billing. CTA store information that will solve problem between client and CSP efficient way the mediator will be responsible to check if the services are provided according to the contract. The mediator will help client and CSP to verify everything .It will act like a third party hence it will be unbiased towards CSP or client.